A cross-linguistic approach to analysing cohesive devices in expository writing by Asian EFL teachers - Hung, Bui Phu; Nguyen, Quang Nhat; Nguyen, Loc Tan; Nguyen, Thi Viet (Penerbit Universiti Kebangsaan Malaysia, 2021)
Recent research has shown that cohesive devices contribute substantially to writing quality and reveal L2 writers’ information, such as first or native language. This quantitative study adopted a cross-linguistic approach to investigating the use of cohesive devices in expository writing by Asian EFL teachers compared to native English teachers. The study involved 80 participants from three different L1 backgrounds, including 28 Vietnamese, 26 Filipino, and 26 native English teachers. The Vietnamese and Filipino teachers were at a comparable level of English proficiency. Around 800 words were randomly selected from each participant’s reports for analysis. Results from One-Way ANOVA showed that the Vietnamese and Filipino teachers used a similar pattern of cohesion with lexical cohesion being used most frequently, followed by reference and conjunction. In contrast, the cohesive devices used by the native English teachers dispersed more widely across five main categories. The results further showed that the native English teachers used more cohesive devices in writing than the Vietnamese and Filipino teachers separately. Results from the Independent-Samples T-test showed omission and redundancy to be the two most common error types by both the Vietnamese and Filipino teachers. The study has implications for L2 writing and pedagogy.